The Relationship Between the Attitude and Achievement in Mathematics for Intermediate Second Class Students - Awad, M. H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Many studies mentioned that there is a decline in the a achievement of intermediate second class students in mathematics  . Parents and mathematics   teachers   had  emphasized   that  .  The  studies   related  this decline to the students weak attitude towards mathematics .In spite  of the  importance  of this subject  , it has not been given enough attention  in research in our country . This research is an attempt to know  th e relationships  between  the  intermediate  second  class  students  , attitude and their achievement  in mathematics .Also, to know the statistical sign ificance of this relationship  according to the gender factor .To verify the research aims , a sample of ( 442) male and female st udents   were   chosen   .  The   mean   scores   of   their   achievement   in mathematics  for  the 1 51   semester  of the academic  year 2002-2003   were obtained  from their schools  . The students'    attitude  was measured  by a scale that was approved  by experts . To analyze the data statistically  , the researcher used number of statistical means . The results showed that :-1-   There   is  a   weak   relationship   between   the   students   attitude towards mathematics  and their achievements  .2-    The  positive   relationship   between  students,   attitude   and  their achievement  among male st udents is better than female students .